Supporting First Grade Students Learning Number Facts Up To 10 Using A Parrot Game - Putra, Zetra Hainul; Darmawijoyo, Darmawijoyo; Hertog, Jaap den; Ilma, Ratu (Journal on Mathematics Education, 2011)
Knowing number facts up to 10 become crucial if we want students to solve addition and subtraction problems using more abbreviated strategies. Otherwise, students will keep counting one-by-one until they get an answer. One of important number facts is number pairs that make ten because it is an important ‘benchmark’ that students will refer to constantly. Considering the important of number facts up to 10, we designed a parrot game activity to supports students learning process. We designed an instructional activity based on Realistic Mathematics Education (RME) approach. We tried this instructional activity with twenty seven first grade students in SDN 179 Palembang. As a result, we found that many first grade students were able to know number facts up to 10, but they still need models to support their thinking.Keywords: number facts up to 10, number pairs that make 10, and parrot game. DOI: http://dx.doi.org/10.22342/jme.2.2.776.163-172